Study on the Level of Aflatoxin M1 Contamination in Raw and Processed Milk Marketed in Kathmandu Valley - Kafle, Pratap; Sedai, Damodar; Rai, Krishna Prasad; Pokharel, Bishow Bandhu (Journal of Food Science and Technology Nepal, 2014)
Aflatoxin M1 (AFM1) is the principal hydroxylated AFB1 metabolite mainly present in milk. In this study the levels of Aflatoxin M1 (AFM1) in Raw and Pasteurized milk marketed in Kathmandu valley was estimated. Altogether 32 milk samples (Raw 16, Pasteurized 16) obtained from different areas of Kathmandu valley were analysed for AFM1 by Thin Layer Chromatography. The milk samples were analyzed according to the official AOAC methods, which included extraction of toxin using chloroform, clearing by silica gel column chromatography, qualitative analysis by Thin Layer Chromatography and quantification by Visual comparison of the spots. AFM1 was found in 14 (43.75%) of milk samples examined. The levels of AFM1 in 7 (21.87%) samples were higher than the maximum tolerance limit (0.05 µg/l) accepted by some European countries while none of the samples exceeded the prescribed limit of US regulations. The mean concentration of AFM1 was higher in Raw milk (0.030 ± 0.042 µg/l) compared to pasteurized (0.022 ± 0.039) but the difference was not statistically significant (p>0.05). This finding reflects that milk marketed in Kathmandu valley contains residual level of Aflatoxin M1 and pose public health risk. Therefore, milk and milk products have to be screened for AFM1 contamination periodically. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10598 J. Food Sci. Technol. Nepal, Vol. 7 (52-56), 2012